The analysis of the information modulation parameters in excess of low-frequency components (kinema) of the speech signal - Zhuravlev, V. M.; Arhypov, O. Ye.; Zhukovyskyi, I. V. (Science and Transport Progress, 2008)
The analysis of informational parameters of modulation of the super-low-frequency speech signal components (kinemas) for whisper speech is realized. It is proved experimentally that in the equiarticulation bands the maximum index of angle modulation that determines the stochasticity of phoneme power amplitude spectrum is much more than one.